Evaluation of potential herb-drug interactions based on the effect of Suxiao Jiuxin Pill on CYP450 enzymes and transporters. (15th November 2021) - Qiang, Tingting; Li, Yiping; Wang, Keyan; Lin, Wenyong; Niu, Zhenchao; Wang, Dan; Wang, Xiaolong
Abstract: Ethnopharmacology relevance: Suxiao jiuxin pill (SJP) is a Chinese medical drug with anti-inflammatory, anti-apoptotic, and vasodilatory function. It is widely used in combination with other drugs for the treatment of coronary heart disease (CHD) and angina. Nevertheless, the effect of SJP on Cytochrome P450 (CYP450) enzymes and transporters' activity related to drug metabolism is rarely studied. Objective: The aim of this study was to investigate the effect of SJP on the activity of drug-metabolizing enzyme CYP450 and transporters. Materials and methods: Human primary hepatocytes were used in present study. Probe substrates of CYP450 enzymes were incubated in human liver microsomes (HLMs) with and without SJP while IC50 values were calculated. The inhibitory effect of SJP on the activity of CYP1A2, 2B6, 2C8, 2C9, 2C19, 2D6 and 3A4 was evaluated. The inducing effect of SJP on the activity of CYP1A2, 2B6 and 3A4 was accessed. The inhibition of SJP on human OATP1B1 was investigated through cell-based assay. The inhibition of SJP on human MDR1 and BCRP was also estimated by means of the vesicles assay. Results: The results showed that the SJP under the concentration of 1000 μg/mL could inhibit the activity of CYP1A2, 2B6, 2C19, and 3A4, with IC50 values of 189.7, 308.2, 331.2 and 805.7 μg/mL, respectively. There was no inhibitory effect found in the other 3 liver drug enzyme subtypes. In addition, SJP showed no induction effect on CYP1A2, 2B6 and 3A4, however it had a significant inhibitory effect on human-derived OATP1B1 at the concentration of 100 and 1000 μg/mL, with the IC50 value of 21.9 μg/mL. Simultaneously, the SJP inhibited BCRP at high concentration of 1000 μg/mL but did not affect human MDR1. Conclusions: Based on these research results above, it is suggested that the SJP can affect some of the CYP450 enzymes and transporters' activity. When used in combination with related conventional drugs, potential herb-drug interactions should be considered. Graphical abstract: Image 1